Mini-incision versus hand-assisted laparoscopic donor nephrectomy in living-donor kidney transplantation: A retrospective cohort study. (May 2018) - Subramanian, Tanvi; Dageforde, Leigh Anne; Vachharajani, Neeta; Wellen, Jason; Doyle, M.B. Majella; Lin, Yiing; Khan, Adeel; Senter-Zapata, Michael; Chapman, William; Shenoy, Surendra
Abstract: Background: Increasing use of Living Donor Kidney Transplantation (LDKT) would decrease the discrepancy between patients awaiting transplantation and organ availability. Minimally invasive surgical approaches attempt to improve outcomes and foster living donation. This report compares outcomes of open minimal incision nephrectomy (Mini N) and a hand assisted laparoscopic nephrectomy (HALN). Methods: This is a retrospective analysis of a prospectively maintained clinical database of LDKT using HALN or Mini N at a single institution between July 2007 and December 2015. Donor and recipient demographics, relevant pre-, intra- and post-operative factors, outcomes such as patient and graft survival rates, and complications were evaluated. Results: Four hundred and fifty-four adult LDKT (243 Mini N, 211 HALN) were performed during the study period. Recipient and donor demographics were comparable except for higher BMI (p = 0.027) in HALN donors. One-, 3- and 5-year patient and graft survival rates were comparable. Six HALN donors experienced infectious wound complications or superficial skin dehiscence; none did in the Mini N group (p = 0.009). Eight HALN donors and one Mini N donor required an incisional hernia repair (p = 0.014). Recipients had similar warm ischemia times (33 v. 35 min, p = 0.491), but recipient surgeons of HALN nephrectomies subjectively noted higher anastomotic difficulty (10.4% v. 4.5%, p = 0.0183). Other parameters were similar between groups. Conclusion: Both Mini N and HALN provide similar long term recipient and donor outcomes. Offering techniques such as Mini N and HALN for living donor kidney procurement facilitates the opportunity to provide living donors safer and better tolerated nephrectomy procedures. Highlights: Mini N and hand assisted laparoscopic nephrectomy (HALN) are reasonable approaches to minimally invasive donor nephrectomy. Minimally invasive surgical approaches foster living kidney donation to address the shortage of transplantable kidneys. Both Mini N and HALN provide similar long term recipient and donor outcomes. Offering both Mini N and HALN for living donor procurement facilitates both provider and patient choice for optimal technique.